Valorization of grape pomace and okara for the development of nutritionally and functionally enriched extrudates: A circular economy approach in snack production - P M, SINDHU; SETHI, SHRUTI; ARORA, BINDVI; JOSHI, ALKA; KUMAR, CHAVLESH; S G, LEKSHMI (The Indian Journal of Agricultural Sciences, 2025)
With the growing emphasis on sustainable development and the circular economy, the valorization of agro-industrial biomass has emerged as a critical strategy to enhance both environmental and economic sustainability. The present study carried out during 2023–24 at ICAR-Indian Agricultural Research Institute, New Delhi reported the development of a novel corn-based extruded snack fortified with grape pomace (GP), a phenolic-rich byproduct of winemaking and okara, an insoluble residue from soybean [Glycine max L. (Merr)] milk and tofu production. Extrusion process optimization was carried out using a Box-Behnken Design (BBD) within the framework of Response Surface Methodology (RSM), considering grape pomace content, feed moisture, and screw speed as independent variables. Optimal extrusion conditions were identified as 7.5% grape pomace inclusion, 11% feed moisture, a screw speed of 300 rpm, and a barrel temperature of 117–121°C, yielding a desirability value of 0.76. Under these conditions, the optimized product demonstrated desirable characteristics, including an expansion ratio of 1.92, porosity of 0.72, total phenolic content of 784.69 mg GAE/100 g, antioxidant activity (FRAP) of 182.47 µmol TE/g, and a sensory acceptability score of 6.54. In addition to improved textural and sensory attributes, the incorporation of GP and okara significantly enhanced the nutritional and functional quality of the product. This work not only valorizes underutilized agro-industrial residues but also contributes to the development of nutritionally improved and environmentally sustainable ready-to-eat snacks.